2021
DOI: 10.2147/ijgm.s292750
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Dysfunction in Patients Admitted in Cardiac Care Unit: Prevalence, Characteristic and Hospitalization Outcomes

Abstract: Introduction Cardiovascular disease is one of the main causes of hospital admission and mortality, and thyroid dysfunction increases the risk of developing acute or exacerbation of chronic cardiac conditions. The aim of this study is to investigate the prevalence of thyroid hormone abnormality among patients in the cardiac care unit (CCU) patients and its relation to admission diagnosis, clinical, biochemical data, and hospital-related outcomes. Methods We conducted a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
0
2
4
Order By: Relevance
“…Furthermore, the frequency of smokers within the study was lower than non-smokers. However, on the contrary, in a study whose smoker participants are higher than non-smokers (3) , another study found fewer smoker rates like ours (14) . Regarding the presence of chronic diseases, hypertension, diabetes mellitus, and dyslipidemia were the most common comorbid conditions as in other studies too (15,17) .…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…Furthermore, the frequency of smokers within the study was lower than non-smokers. However, on the contrary, in a study whose smoker participants are higher than non-smokers (3) , another study found fewer smoker rates like ours (14) . Regarding the presence of chronic diseases, hypertension, diabetes mellitus, and dyslipidemia were the most common comorbid conditions as in other studies too (15,17) .…”
Section: Discussioncontrasting
confidence: 78%
“…The most common causes of admission in our study were acute coronary syndrome and arrhythmia, but in other studies, the most common causes were acute coronary syndrome and decompensated heart failure (14) .…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…One local study concluded that there was no significant association between hypothyroidism and CAD. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%